Predicting financial status of healthcare and property sector in Malaysia - Rosle, Alia Nadira; Ismail, Munira; Abdul Razak, Fatimah; Bahaludin, Hafizah (AIP Publishing, 2024)
In 2020, the rapid and widespread impact of COVID-19 as a severe public health threat affected countries worldwide, causing significant social and economic disruptions. This preliminary study examines the financial conditions of the healthcare and property sectors in Malaysia before and during the COVID-19 pandemic by using the Altman Z-score. The study sample includes 20 healthcare companies and 81 property companies listed on the Kuala Lumpur Stock Exchange between 2018 and 2021, as extracted from Eikon DataStream. It was discovered that most healthcare companies were financially secure both before and during the COVID-19 pandemic, whereas most property companies were in financial distress even before the pandemic began. These findings suggest that the healthcare sector was more stable than the property sector before and after the COVID-19 pandemic.